Karnataka Annual Plan 1982-83 Volume-V Tribal Sub-Plan - Planning Commission (Planning Commission, 1982)
Tribal Sub-plan is a part of the State plan in res cot of each development department involved in implementing the schemes for the development of Tribals. Funde for the implemention of schemes arc met out of the State Plan, the Central Government also provides special Central Assistance to supplement the state's efforts towards the development of the tribals in the tribal, sub-plan area. This area covers tribal habitants and its geographical location as indicated elsewhere below.
Planning Department